Pengaruh Ekstrak Pemberian Tumbuhan Meniran terhadap Kesehatan - Anang Kurniawan; Alya Afriana Syahrani; Annatsa Yolantiara Mahanani; Desianti Cahya Nugraheni; Maulana Rahmadani; Liss Dyah Dewi Arini (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Meniran Meniran (Phyllanthus niruri L.) contains bioactive compounds that are able to inhibit bacterial growth (antibacterial) and kill bacteria. This research aims to determine the effect of the concentration of extract Phyllanthus niruri L. and the effective concentration of Phyllanthus niruri L. which can inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria. The test bacteria used were Staphylococcus aureus and Escherichia coli. This research was experimental using a completely randomized design (CRD) with 11 treatments consisting of extract concentrations of 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100% with 3 repetitions for each bacteria. The data obtained in this study were analyzed using Single Anova and further tests using BNT 5%. Based on the research results, it shows that there is an effect of giving extract of Phyllanthus niruri L. on the growth of Staphylococcus aureus and Escherichia coli bacteria and the concentration extract of Phyllanthus niruri L. that effectively inhibits the growth of Staphylococcus aureus bacteria is 80% while the effective concentration is able to inhibit the growth of Escherihcia coli bacteria is 90%.